Effective Communication in Business - Ayob, Arshad (Journal of Modern Languages, 2017)
This study deliberates the need for effective commination in business, by considering the role of ‘to influence the thinking of others’, as a type of communication. Influencing the thinking of others, is a critical matter that determines the effectiveness of business executive. To be able to communicate and motivate others to favourable action is the very essence of business management, which is considered in this paper.